The Influence Service Quality and Corporate Image on Customer Satisfaction at PT POS Indonesia - Faif Yusuf; Dhea Aprilia (Syntax Corporation Indonesia, 2023)
The purpose of this study was to see the effect of Service Quality and Corporate Image on Customer Satisfaction. with the Random sampling technique as a determinant of the number of respondents indicated for customers of PT. Post Indonesia (Persero) West Jakarta Post Office, where this data collection method uses a questionnaire. Testing is done with Multiple Regression by testing the classical assumptions first, then testing the hypothesis partially with the t test and simultaneously with the f test. then look for the coefficient of determination to see how much the proportion of independent variables affects the variable bond. The results of the study stated that simultaneously (Test F) the independent variables studied, namely Service Quality and Corporate Image, had a positive and significant effect on Customer Satisfaction. While the results of the partial test (T test) Service Quality has no positive effect on Customer Satisfaction and Corporate Image has a positive and significant effect on Customer Satisfaction with a fairly large determination coefficient value of 74.3% and the rest is influenced by other variables not examined in this study.